A shapeable, ultra-stretchable rubber strain sensor based on carbon nanotubes and Ag flakes via melt-mixing process. Issue 16 (24th March 2021) - Zhang, Qiang; Pan, Shirui; Ji, Chao; Song, Jianqiao; Zhang, Rui; Zhang, Wendong; Sang, Shengbo
Abstract : Promoting the detection range, durability, and shapeable manufacturing of flexible strain sensors is essential to broaden their applications. Abstract : Promoting the detection range, durability, and shapeable manufacturing of flexible strain sensors is essential to broaden their applications. Therefore, in this study, styrene ethylene butylene styrene (SEBS) rubber as a flexible material and a melt-mixing molding method are adopted to design an ultra-flexible strain sensor. Carbon nanotubes (CNTs) are added to form a conductive network, and the effect of Ag flakes on improving the sensor performance is studied. The experiment results exhibit good strain–resistance dependent characteristics of the obtained sensor, which demonstrates an excellent sensing range of about 540% with a gauge factor (GF) of 5.197. The good hydrophobicity (water contact angle ≈120.4°), repeatable characteristics at different rates, strain-dependence and long-term recycling of the sensor are demonstrated as well. Finally, the fabricated round bracelet sensor is applied to detect different cross-sections, the movement of human joints, balloon inflation, bottle cap sealing and numerous other aspects.